James Parkinson and his essay on “shaking palsy”, two hundred years later - Leonardo Palacios-Sánchez; Martha Torres Nupan; Juan Sebastián Botero-Meneses (Arquivos de Neuro-Psiquiatria)
ABSTRACT In 1817, British physician James Parkinson published a 66-page document entitled “Essay on the Shaking Palsy”. This brief text became a classical and fundamental piece in the history of medicine and, in particular, of neurology. The authors of this article wish to pay tribute to this great pioneer of neurology, 200 years after the publication of his findings, which would, in turn, immortalize his name and give rise to the renaming on the entity in 1860 by Professor Jean Martin Charcot, father of neurology. It would be known, henceforth as Parkinson’s disease.